Assessable learning outcomes for the EU Education and Training Framework core and Function A specific modules: Report of an ETPLAS WORKING Group. (June 2021) - Dontas, Ismene A; Applebee, Kenneth; Vlissingen, Martje Fentener van; Galligioni, Viola; Marinou, Katerina; Ryder, Kathy; Schenkel, Johannes; Prins, Jan-Bas; Degryse, Anne-Dominique; Lewis, David I
Article 23(2) of the European Union Directive 2010/63/EU, which regulates welfare provisions for animals used for scientific purposes, requires that staff involved in the care and use of animals for scientific purposes be adequately educated and trained before they undertake any such work. However, the nature and extent of such training is not stipulated in the Directive. To facilitate Member States in fulfilling their education and training obligations, the European Commission developed a common Education and Training Framework, which was endorsed by the Member States Competent Authorities. An Education & Training Platform for Laboratory Animal Science (ETPLAS) Working Group was recently established to develop further guidance to the Learning Outcomes in the Framework, with the objective to clarify the levels of knowledge and understanding required by trainees, and to provide the criteria by which these Learning Outcomes should be assessed. Using the Framework document as a starting point, assessment criteria for the Learning Outcomes of the modules required for Function A persons (carrying out procedures on animals) for rats, mice and zebrafish were created with sufficient detail to enable trainees, providers and assessors to appreciate the level of knowledge, understanding and skills required to pass each module. Adoption and utilization of this document by training providers and accrediting or approving bodies will harmonize introductory education and training for those involved in the care and use of animals for scientific purposes within the European Union, promote mutual recognition of training within and between Member States and therefore free movement of personnel.